Risk Factors Associated with Hemoparasites in Dual-Purpose Cattle of Colombia - César A. Murcia-Mono; Sergio Falla-Tapias; Andrés F. Morales Cabrera; Laura C. Navia Álvarez; Leidy Rivera-Sánchez; Yolanda Gómez Vargas; William O. Burgos-Paz (Pathogens)
Hemoparasitic diseases represent a significant problem with a considerable impact on tropical and subtropical areas of the world. These conditions cause economic losses associated with multi-organic failure and even the death of animals. In these areas, the hemoparasites are transmitted in an enzootic cycle when infectious cattle, such as persistently infected animals, including cows, contribute to the success of transmission. However, the factors associated with transmission have always been considered environmental issues, disregarding herd management and practices. In this sense, we conducted a cross-sectional study sampling 360 female cattle older than one year to identify infectious cattle using the PCR technique. We employed a dichotomic questionnaire for association analyses in 150 herds of the southern Andean region of Colombia. Overall prevalence with infectious cattle was 52.5% for Babesia spp., Anaplasma spp., and Trypanosoma spp., and the significant risk factors (p < 0.05) included geographic area, animal weight, purchase of cattle for fattening, disinfection of clothing after contact with neighboring animals, self-medication, separation of animals in pens, supply of mineralized salt, presence of livestock from other owners on the farm, prevention of joint trauma, documented milking routine, and sending blood samples for analysis. These practices permitted the maintenance of persistently infected animals and their movement to shed the agents to other animals in the presence of vectors. This suggests the importance of implementing comprehensive control and training measures to reduce the infectious cattle and, therefore, the profitability of dual-purpose livestock farms in the Andean region of southwestern Colombia.